Clinical heterogeneity in a family with flail arm syndrome and review of hnRNPA1‐related spectrum. Issue 12 (31st October 2022) - Han, Xiaochen; Zhan, Feixia; Yao, Yuxin; Cao, Li; Liu, Jianguo; Yao, Sheng
Abstract: Objective: Flail arm syndrome (FAS) is one of the atypical subtypes of amyotrophic lateral sclerosis (ALS). Mutations in hnRNPA1 encoding heterogeneous nuclear ribonucleoprotein (hnRNP) A1 are a rare genetic cause of ALS. Herein, marked clinical heterogeneity of FAS in a pedigree with a known hnRNPA1 variant was described to raise early awareness of the ALS variant. Furtherly, a literature review of the hnRNPA1 ‐related spectrum was made to summarize the clinical and genetic characteristics. Methods: Detailed clinical evaluation, muscle pathology, and whole‐exome sequencing were performed. The sequence and co‐segregation of the mutation among the family members were confirmed by Sanger sequencing. Results: The great clinical variability was found in a FAS pedigree. Muscle pathology revealed a cluster distribution of angulated or rounded atrophic fibers, accompanied by significant multi‐nucleus aggregation. Immunohistochemical staining showed that mutant hnRNPA1 proteins accumulated in muscle fiber cytoplasm. Exome sequencing identified a documented variant in hnRNPA1 gene c.1018C > T (p.P340S), which co‐segregated with disease in the family. Besides, highly phenotypic heterogeneity was also found in other hnRNPA1 ‐related diseases. Interpretation: We described a Chinese pedigree with hnRNPA1 ‐related FAS, which showed significant clinical variability among the intrafamilial members. FAS is a relatively milder variant of ALS, due to the highly heterogeneous clinical spectrum, early observation is of paramount importance. In addition, the highly phenotypic heterogeneity and molecular genetic mechanism of the hnRNPA1 ‐related spectrum are still beyond fully understood. Further, the detailed molecular mechanism underlying the clinical diversity is warranted to be explored.